Pemberdayaan Kepala Dusun Desa Belah Melalui Program Pelatihan Dasar Penggunaan Microsoft Word - Ghani, Farid Abdul; Acyutarayi, Rakashafi Noorsy; Putri, Kika Fidiyah; Khotimah, Khusnul; Dini, Putri Indra; Widhaningrum, Tivani Nuri; Adhitya, Fajar; Marjani, Zaidan Isham; Hanani, Hayyu Amalina; Tsany, Dylan Ataa; Wisnujati, Andika (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Increasing the capacity of village officials in the use of information technology is a strategic step in accelerating village government administration. Hamlet heads, as part of the village apparatus, need to have basic skills in digital document management in order to improve work efficiency. This basic Microsoft Word training program aims to empower hamlet heads in Belah Village, Donorojo District, Pacitan, by providing understanding and practical skills in creating and managing documents. This training was attended by 12 participants and used practice-based learning methods, interactive discussions, and direct assistance. Evaluation was carried out through a survey of participants to measure the effectiveness of the training. The survey results showed that 83% of participants felt that their skills had improved significantly, especially in the use of basic Microsoft Word features such as text formatting, table creation, and image insertion. As many as 75% of participants stated that this training was very relevant to their administrative tasks, while 92% expressed interest in taking further training. These results indicate that the training program has a positive impact on improving the competence of hamlet heads in document management. It is hoped that the sustainability of this program can support more effective and efficient village administration